Effect of different qualities of foam on fill particle transport in horizontal well cleanup operation using coiled tubing - Khan, J.A. (2014)
This study focuses on the effect of foam quality on fill concentration during coil tubing cleanup operation. Thus, to quantify such effect, it is required to develop the numerical model to investigate the well cleaning. ANSYS CFX-14 is used for numerical study of fill transport in the horizontal well. A horizontal well geometry (5.76â³Ã3.5â³ concentric annulus) was created for fill concentration analysis. Present study is carried out with 70, 80 and 90 quality at four different velocities 3, 4, 5 and 6 ft/sec. The results indicated that the 90 quality foam was good even at low velocity. Â© (2014) Trans Tech Publications, Switzerland.